Some Observations on the Rôle of Hageman Factor in Blood Coagulation - Haanen, C; Hommes, F; Morselt, Gerdy (Thrombosis and Haemostasis, 1961)
The defective thromboplastin formation in Hageman factor deficient plasma is completely corrected using incubation tubes which have been coated previously with normal plasma. Positively or negatively charged molecules as protamin and sulphated polysaccharides interfere with this correction in a way that gives evidence Hageman factor is a positively charged protein.The defective thromboplastin generation of Hageman factor deficient incubation mixtures is corrected by addition of a purified Hageman factor preparation. Pre-incubation of Hageman factor with HF deficient serum improves the thromboplastin formation further, while pre-incubation of Hageman factor with HF deficient plasma abolishes this correction complete. Possibly here lies the key for the fact that serum clotting factors augment and plasma factors deteriorate during the clotting process.